A exposição peripuberal ao herbicida à base de glifosato influencia o efeito da dieta hiperlipídica no músculo diafragma de camundongos adultos - Marca, Ana Paula (2021)
The Developmental Origins of Health and Disease studies the effects caused by insults at critical periods of development (fetal, neonatal and puberty), which can compromise health throughout life. Glyphosate is an organophosphate herbicide, with endocrine-disrupting and modulatory effects on puberty. Exposure to pesticides in critical periods of development is related to obesity in adulthood. Obesity is characterized as a high level of body fat, which compromises the function of several systems. Thus, the aim of this study was to analyze the effects of peripubertal exposure to glyphosate-based herbicide (GBH) on the histomorphometry of muscle fibers and neuromuscular junctions (NMJs) of the diaphragm muscle of obese or non-obese adult mice. Twenty-two male mice from C57BL/6 strain were used and separated into groups according to the exposure to GBH and high-fat diet. Exposure to GBH occurred from 30 to 60 days by gavage, at a dosage of 50 mg/kg/day of Roundup™. The high-fat diet was offered from 60 to 150 days, therefore, 4 groups were formed: Control Group (CTL, n=6); Glyphosate-based Herbicide Group (GBH, n=6); Control High-Fat Diet Group (DH-CTL, n=5); and High-Fat Diet And Glyphosate-based Herbicide Group (DH-GBH, n=5). At 150 days, the animals were euthanized and weighed, both retroperitoneal and perigonadal fats and the diaphragm were collected and weighed. Muscle fragments were stored in specific fixatives for the histological study of muscle fibers and NMJs. Comparing the GBH and the CTL groups, there was a reduction in the body weight of the GBH animals. Rounded, hypereosinophilic fibers and enlarged nuclei were observed in both groups, but predominantly in the GBH. In the GBH group, there was an increase in the area, larger and smaller diameter of muscle fibers and in the area and larger diameter of NMJs, an increase in type III collagen and a decrease in the overlap of type I and III collagen. Regarding the DH-CTL and DH-GBH groups, rounded, hypereosinophilic fibers and cytoplasm vacuolization were evident in both groups, however, more pronounced in the DH-GBH. Both longitudinally split and hypertrophic fibers were visualized only in the DH-GBH. There was an increase in the area and larger diameter of NMJs in the DH-GBH group. It is concluded that peripubertal exposure to GBH resulted in morphological changes that are characteristic of muscular degeneration, and altered the morphometry of muscle fibers in non-obese adult mice, altered the morphometry of diaphragm NMJs in obese and non-obese adult mice and exacerbated the degenerative changes in the diaphragm muscle of obese adult mice.